A New Stability Indicating RP-UFLC Method for the Estimation of Letrozole in Presence of Internal Standard - Annapurna, Dr. Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Letrozole is an anti-cancer agent especially used for the treatment of estrogen-dependent breast cancers. A new stability indicating reversed-phase ultra-fast liquid chromatography (RP-UFLC) method has been proposed for the estimation of Letrozole in tablet dosage forms. Materials and Methods: Shimadzu Model UFLC system with PDA detector and Luna C8 column with mobile phase mixture methanol: Acetonitrile: 0.1% aq. acetic acid (10: 40: 50) with flow rate 1.0 mL/min was chosen on isocratic mode (Detection wavelength 255 nm). Results and Discussion: Letrozole obeys Beer–Lambert’s law over the concentration range 0.05–100 μg/mL with linear regression equation y = 3679×–0.0002 (R² = 0.9999). The limit of quantification and limit of detection were found to be 0.0158 μg/mL and 0.0484 μg/mL. Stress degradation studies were performed such as acid hydrolysis, alkaline hydrolysis, thermal treatment, and oxidation and the method was validated as per ICH guidelines. The proposed RP-UFLC method was applied for the quantification of pharmaceutical formulations (Tablets) and found to be simple, precise, accurate, and robust. Conclusion: The proposed RP-UFLC method was applied for the quantification of pharmaceutical formulations (Tablets) and found to be simple, precise, accurate, and robust.